Defining user risk in social networking services. Issue 1 (19th January 2015) - Haynes, David; Robinson, Lyn
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to identify the risks faced by users of online social networking services (SNSs) in the UK and to develop a typology of risk that can be used to assess regulatory effectiveness. Design/methodology/approach – An initial investigation of the literature revealed no detailed taxonomies of risk in this area. Existing taxonomies were reviewed and merged with categories identified in a pilot survey and expanded in purposive sample survey directed at the library and information services (LIS) community in the UK. Findings – Analysis of the relationships between different risk categories yielded a grouping of risks by their consequences. This aligns with one of the objectives of regulation, which is to mitigate risks. Research limitations/implications – This research offers a tool for evaluation of different modes of regulation of social media. Practical implications – Awareness of the risks associated with use of online SNSs and wider social media contributes to the work of LIS professionals in their roles as: educators; intermediaries; and users of social media. An understanding of risk also informs the work of policy makers and legislators responsible for regulating access to personal data. Originality/value – A risk-based view of regulation of personal data on social media has not been attempted in such a comprehensive way before.